(untitled) (Kronika Bydgoska, 2010)
Sports architecture was the background for different type events, both sports and cultural ones, and sports facilities often manifested their modemity and technological domination. Bydgoszcz is a city of numerous cyclic events and occasional intemational sports events. Each such event reąuires ade- ąuate space and facilities. That’s the reason for new sports and entertainment investment projects planned in the city. However, many of the prepared projects have remained on carbon paper, e.g. the “Górzyskowo” Centre Sport Hall project in Bydgoszcz, which was to be constructed by the intersection of Żwirki i Wigury and Jaskółcza Streets, and the sports and entertainment hall with an arena - skating rink for 6,500 spectators, a bowling arcade, a hotel-administrative complex, and training rooms, which was to be located in an area limited by the Brda River and Toruńska Street. These facilities have never been constructed and today we can admire them on yellowed carbon papers only.